A Descriptive Study of the Difficulties in Using Regular and Irregular Verbs in Simple Past Tense of the Eighth Grade Students at SMP Muhammadiyah 3 Banyuwangi - Annisa Oktaviani; Nur Hasibin (LUNAR, 2020)
The research design of this study was descriptive. The objective of this thesis was to know the difficulties of the students in using regular and irregular verbs in simple past tense. This research was conducted in SMP Muhammadiyah 3 Banyuwangi in which the respondents were the eighth year students. They were chosen by population technique. The number of respondents in this research was 136 students. In this research, the researcher used a test as the main method of collecting data. To analyze the collected data, the reearcher used percentage method. They are 136 students as the research sample which was taken by using population. It means the Eighth Grade from VIII A to VIII E. Based on the result of the data analysis, it can be known the percentage of the students’ difficulties in using regular and irregular verbs in simple past tense is 47,5%. The number of the students that chose incorrect answer almost equal with the number of the students that chose correct answer. It shows that many students were still having difficulties in using regular and irregular verbs in simple past tense.